Empirics on the causal effects of rent control in Germany - Andreas Mense; Claus Michelsen; Konstantin A. Cholodilin (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
This paper empirically analyzes the effects of a second generation rent control. We make use of an uncommon policy intervention in the German housing market and translate the generated variation into a difference-and-differences setup, augmented with elements of a discontinuity design, to identify the causal impact of rent controls. We exploit the spatial and temporal differences in the regulation, finding significant effects on de facto regulated and unregulated rents and house prices. Our results suggest that the regulation benefits low/medium income households. Further, we provide evidence that rent regulations alter land values and depress maintenance activities. Overall, these results fit the predictions of a standard comparative-static representation of a second-generation rent control, which sheds a more favorable light on housing market interventions.
Keywords: D2; D4; R31; 330; housing policy; rent control; rental housing; Germany